Challenging Cases in Cerebrovascular Disease - Kelly, Michael A.; Singh, Jasmine; Balabanov, Alexandra; Wadina, Adam; Dasovic, Braden (Seminars in Neurology, 2022)
Disorders involving the vascular system of the brain are numerous and sundry. Atherosclerotic thromboembolism of large vessels and lacunar infarctions of small vessel disease are well known. Brain infarction due to cardioembolism is common as well, and even more so when diligently sought. Rupture of intracranial blood vessels results in subarachnoid and intraparenchymal hemorrhage. We present four cases of stroke of uncommon cause and remind clinicians to be open minded to the many possible causes of stroke, in particular because early recognition and treatment is often critical. Case 1 discusses a patient with inflammatory cerebral amyloid angiopathy. The presentation, ability to recur, and current treatment considerations are reviewed. Case 2 discusses microangiopathic thrombotic angiopathy. Diagnosis and treatment are considered. An association with interferon therapy and the evolving terminology of this and related conditions are discussed. Case 3 discusses intracranial hemorrhage secondary to acute promyelocytic leukemia. Patients with acute leukemias require aggressive management of their coagulopathy, thrombocytopenia, and the disease itself. Finally, Case 4 discusses ischemic stroke due to a paradoxical embolism in the setting of a patent foramen ovale (PFO). Both medical and surgical management of a PFO for stroke prevention are considered.
Keywords: cerebral amyloid angiopathy; microhemorrhage; thrombotic microangiopathy; interferon therapy; acute promyelocytic leukemia; patent foramen ovale